Serum inflammation-related proteins in a acute compartment syndrome rat model - Tao Wang; Jingcheng Cao; Zhiyong Hou; Qi Zhang (Scientific Reports)
Abstract We aim to explore variations of serum inflammation-related proteins in an acute compartment syndrome (ACS) rat model. We collected serum from 25 healthy Sprague-Dawley rats (control group, CG) and 50 rats with tibial fractures, including 25 rats with ACS (ACS group, AG), and 25 rats without ACS (fracture group, FG). Ten samples per group were randomly chosen for proximity extension assay analysis of 92 inflammation-related proteins, and all samples were verified by enzyme-linked immunosorbent assays. Receiver-operating characteristic curve analysis was used to identify the diagnostic ability and cut-off values. Our findings showed that the levels of Il6 and Prdx5 in the FG and Il6, Prdx5, Dctn2, and Plin1 in the AG, were significantly higher than those in the CG. Notably, compared with the FG, high expression of Prdx5, Dctn2, and Plin1 was observed in the AG. Additionally, we identified 58.8764, 14.023, and 31.8730 pg/ml as the cut-off values of Prdx5, Dctn2, and Plin1 to predict ACS in rats. Similarly, the cut-off values of Il6, Prdx5, Dctn2, and Plin1 to predict ACS in healthy rats were 10.6783, 766.5879, 12.5627, and 14.3623 pg/ml, respectively. Furthermore, the combination of these proteins had the highest diagnostic accuracy. We identified Prdx5, Dctn2, and Plin1 as potential biomarkers of ACS compared with fracture in rats and revealed that combination of Il6, Prdx5, Dctn2, and Plin1 had the highest diagnostic accuracy to predict ACS compared with the healthy condition. Furthermore, the cut-off values for these biomarkers were determined, providing a new method to rapidly assess the risk of ACS and manage early targeted interventions.